Analisis Kualitas Layanan Teknologi Informasi pada Domain Service Operation dengan Pendekatan Framework ITIL V.3 (Studi Kasus: Website Kampus Merdeka) - Arribe, Edo; Azura, Yollanda; Muslim, Nurul Alifa Putri; Nurfadhilah, Nabila; Wulandari, Febrilyana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The Independent Campus programme, which allows students to take courses outside their programme of study and participate in activities outside the university, has experienced rapid growth. However, this growth brings a number of challenges, such as increased data volume, high service demands, and IT infrastructure complexity. The performance and responsiveness of IT services is also a concern, given users' expectations for fast performance. Effective customer support is also required to ensure a satisfactory user experience. To address these issues, an analysis of information technology (IT) management using the ITIL V3 framework in the Service Operation domain was conducted. The results of the analysis show that incident management, service requests, problems, access, and service operations can be improved through the implementation of ITIL. It helps improve operational efficiency, reduce the impact of incidents and problems, accelerate request fulfilment, maintain access security, and improve the quality and availability of IT services. The implementation of ITIL V3 is an important step in supporting the success of the Kampus Merdeka Programme in providing better access to education for students in Indonesia. Thus, the implementation of ITIL V3 is an important step in supporting the success of the Merdeka Campus Programme in providing better access to education for students in Indonesia.